2018
DOI: 10.1016/j.jhin.2018.06.026
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of national strategies to reduce meticillin-resistant Staphylococcus aureus infections in Japan and England

Abstract: Background: National responses to healthcare-associated infections vary between high-income countries but when analysed for contextual comparability, interventions can be assessed for transferability. Aim: To identify learning from country-level approaches to addressing meticillin-resistant Staphylococcus aureus (MRSA) in Japan and England. Methods: A longitudinal analysis (2000-17), comparing epidemiological trends and policy interventions. Data from 441 textual sources concerning infection prevention and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 29 publications
(27 reference statements)
0
10
0
Order By: Relevance
“…Infections caused by MRSA have been prevalent in many countries for decades even if in recent years, the prevalence of some serious infections, such as bloodstream infections (BSI), have declined [3,4]. Data from the UK and Northern Ireland from 2010-2014 derived from mandatory reporting of S. aureus bloodstream infection has shown that the proportion of BSI due to S. aureus has fallen from 16.2% to 8.9% with a downward trend in all four countries [3].…”
Section: Introductionmentioning
confidence: 99%
“…Infections caused by MRSA have been prevalent in many countries for decades even if in recent years, the prevalence of some serious infections, such as bloodstream infections (BSI), have declined [3,4]. Data from the UK and Northern Ireland from 2010-2014 derived from mandatory reporting of S. aureus bloodstream infection has shown that the proportion of BSI due to S. aureus has fallen from 16.2% to 8.9% with a downward trend in all four countries [3].…”
Section: Introductionmentioning
confidence: 99%
“…Key stakeholders may then work proactively to formulate contingent strategies particularly where wider influences carry high levels of uncertainty. For example, in countries which perform well in the economic domain, the factors in the political domain can still hinder progress; notably, in Japan, five terms of office, seven general elections since 2000 and an average length of 1.9 years of office (July 1998 and December 2017) may need reliance on strengthening the other domains for sustainable solutions 39…”
Section: Discussionmentioning
confidence: 99%
“…Daptomycin (DAP) is active against S. aureus including MRSA (8). Several studies have suggested the clinical utility of DAP in diabetes patients (6,(9)(10)(11)(12)(13).…”
Section: Accepted Manuscript Introductionmentioning
confidence: 99%